THE ABILITY IN WRITING SIMPLE PAST TENSE OF VIII A SMP ANGKASA KUTA’S STUDENT - Si Putu Agung Ayu Pertiwi Dewi (SPHOTA: Jurnal Linguistik dan Sastra, 2016)
ABSTRACT This writing discuses about the phenomenon that mostly happen during English session at VIII A class in SMP Angkasa Kuta. The problems occurred when the students tried to write the sentence. They found the difficulties in using regular and irregular verb form, using of copula be, using of adverb of time and using of negative form in past tense. This study was classroom action research that collected descriptive data. The data collected by taking the sample of student sentences and analyzed the student ability in writing simple past tense. Based on the observation, there were two kinds of factors influences the student ability in writing simple past tense of VIII A SMP Angkasa Kuta’s student. First, The internal factors were made by the student itself. It impeded learning process in class during the English session. Second, the external factor came from the monotone teaching style and the situation. Keywords:ability,simple past tense, writing,